2020
DOI: 10.1051/e3sconf/202016800031
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and methodological support for Ukrainian coal enterprises marketing activity improvement

Abstract: The tendencies of marketing policy development in some world’s mining countries in the light of global transformational changes are considered. The factors influencing the marketing activity of Ukrainian coal mining enterprises are identified. The volumes and structure of coal consumption in Ukraine are analyzed with a purpose to identify trends of demand volatility and specifics of logistics services for different consumer categories. It is substantiated the expediency of marketing networks formation as a for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…Dkhili (2018) confirmed the link between environmental performance and the country's development using GDP as a key indicator of economic growth. Paj ąk et al (2017), Miskiewicz (2018), Kwilinski et al (2020aKwilinski et al ( , 2020b, Dzwigoł et al (2019) and Saługa et al (2020) analysed energy security as the key indicator of the economic growth. Vasylieva et al (2019) and Bilan et al (2019) confirmed that the spread of renewable energy reduces GHG emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Dkhili (2018) confirmed the link between environmental performance and the country's development using GDP as a key indicator of economic growth. Paj ąk et al (2017), Miskiewicz (2018), Kwilinski et al (2020aKwilinski et al ( , 2020b, Dzwigoł et al (2019) and Saługa et al (2020) analysed energy security as the key indicator of the economic growth. Vasylieva et al (2019) and Bilan et al (2019) confirmed that the spread of renewable energy reduces GHG emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [43][44][45][46][47][48][49][50][51][52][53][54][55] analysed the options of the industrial companies to implement green technologies. They proved the hypothesis that green technology of electricity production allows reducing the cost and increasing the company's profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as a result of research (Nyenno et al 2020;Ivanov et al 2019;Kwilinski et al 2020;Liashenko et al 2021;Trushkina et al 2021;Dźwigoł et al 2021aDźwigoł et al , 2021b the conceptual approach to the cluster formation as a specific type of partnership of energy companies, business structures, research institutions, higher education institutions, institutions of logistics, energy and innovation infrastructure, government agencies and authorities are substantiated. Self-government on the basis of green and circular economics, application of the methodology for developing a smart specialization strategy, the introduction of digital technologies and logistics concepts, use of modern financial instruments (venture investment, crowdsourcing, public-private partnership by calling in private investment, credit organizations, pension funds, grants.…”
Section: Conceptual Approach To the Formation Of The Eco-energy Clustermentioning
confidence: 99%